PERANAN AERASI DAN SILIKA SERTA LAMA PEMERAMAN TERHADAP KANDUNGAN UNSUR HARA PUPUK CAIR LUMPUR ORGANIK UNIT GAS BIO - Mochammad Junus; Agung Sugeng Widodo; Wahyono suprapto; Windi Zamrudy (TERNAK TROPIKA Journal of Tropical Animal Production, 2014)
Organic sludge biogas unit (OSBGU) is an organic product that is generally overlooked by the owner. Giving aeration and silica as treatment with longer curing 1, 2, 3, 4 and 7 days for prospective OSBGU liquid fertilizer is expected to change the percentage of the nutrient content of liquid manure OSBGU candidates become better liquid fertilizer. The results showed that the effect of treatment, curing time and the interaction between the percentage of liquid manure nutrient content OSBGU on posphor (P), potassium (K), sodium (Na) and calcium (Ca) was significantly different. Conclusion: The role of aeration and the addition of silica as well as their interactions and their long ripening turns very significant effect on the percentage of the nutrient content of liquid fertilizer OSBGU. Suggestion: to make the aeration and the addition of silica to the fermentation time to increase the percentage of liquid manure nutrient content OSBGU should use aeration and if necessary by adding silica and brooded until on day 7